FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING - Mariati, Rusda; Tunggal, Tri; Dewi, Vonny Khresna; Yuliastuti, Erni (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Stunting is a very serious nutritional problem that can occur in toddlers. The incidence of stunting at the Amuntai Selatan Health Center in 2024 was 19.22%. Several factors that influence the incidence of stunting are mostly minimal maternal knowledge, history of breastfeeding and history of low birth weight (LBW). Objective: To find out the factors related to the occurrence of stunting in the Amuntai Selatan Health Center work area. Methods: The design of this study is observational analytic with a cross-sectional approach. The sampling technique used accidental sampling with a sample size of 95 people. Data analysis used the Chi-Square test. Results: The incidence of stunting in toddlers was 27 toddlers (28.4%). Mothers with sufficient knowledge were 43 people (45.3%). Toddlers with a history of exclusive breastfeeding were 53 people (55.8%). Toddlers with a history of non-LBW (≥2500 grams) were 75 toddlers (78.9%). Conclusion: There was a correlations between maternal knowledge (ρ=0.024), history of exclusive breastfeeding (ρ=0.020) and history of LBW (ρ=0.000) with the incidence of stunting in the Amuntai Selatan Health Center work area. It is expected that the Health Center can improve the programs that have been implemented, add information related to stunting. Evaluation of the stunting handling program needs to be carried out periodically.